Problems of Islamic Primary and Secondary Education in Era 4.0 In Indonesia - Ayu Umi Prihatin; Subiyantoro Subiyantoro (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article aims to determine the policies and problems that exist in Islamic primary and secondary education in Indonesia in Era 4.0. This research method uses library research with a qualitative approach. The authority of schools to manage themselves is given by the government to develop the potential that exists in schools so that there are several things that are the duty of the government in terms of education, one of which is education management as stated in Law no. 23 of 2014 that the district or city government manages basic education. The national education policy for Islamic basic education includes Madrasah Ibtidaiyah and Madrasah Tsanawiyah which have been regulated in Minister of Religion Regulation No. 60 of 2015 concerning the Implementation of Madrasah Education, paragraphs 4 and 5. Then the national education policy on secondary education includes Madrasah Aliyah and Vocational Madrasah which have been regulated in Minister of Religion Regulation No. 60 of 2015 concerning the Implementation of Madrasah Education, paragraphs 6 and 7. The educational levels of MI, MTs, MA, and MAK are all under the auspices of the Minister of Religion. Islamic primary and secondary education in Indonesia in Era 4.0 include First, the lack of public interest in Islamic education. Second, the low quality of teachers, Third, government discrimination against the allocation of Islamic education funds. Fourth, Certificate oriented. Fifth, the low quality of each learning process management process in each educational unit.